The antiviral activity of srikaya seed (Annona squamosa L.) ethanolic extract against newcastle disease virus in chicken embryo - Nanik Sulistyani (Indonesian Journal of Pharmacy, 2009)
Srikaya (A. squamosa L.) is a plant containing polyphenol, flavonoid, tannin, alkaloid and saponin compounds. These compounds could be extracted by ethanol solvent. Previous study shown that infuse of Srikaya seed had antiviral activity with value of IC50 3,236 'g/mL against Newcastle Disease Virus (NDV). Therefore, the aim of research is to know the potency of ethanolic extract of Srikaya seed as antiviral against Newcastle Disease Virus.The 28 chicken embryos at age of 9-11 days were classified into 7 groups, i.e. : control of virus, control of solvent ethanol : aquadest (1:10) and treatment groups were given ethanolic extract of Srikaya seed with concentration 0.1 'g/mL; 0.15 'g/mL; 0.2 'g/mL; 0.25 'g/mL; dan 0.3 'g/mL. NDV was inoculated into allantoic cavity intermediate after inoculated of extract and thenincubated for 2 days. Antiviral activity were observed by hemaglutination method. The value of IC50 was calculated by probit analysis.The result showed that ethanol extract of srikaya seed (A. squamosa L.) had antiviral activity because of increasing concentration caused the higher inhibition percentage of hemaglutination. The value of IC50 is 0.152 'g/mL.Key words: Antiviral, Annona squamosa, Newcastle Disease Virus (NDV).